Ex traditione, innovatio: la tradición que funda, la juventud que transforma - García Belaunde, Domingo (2025)
On the occasion of the sixtieth anniversary of THĒMIS, this interview gathers the founder’s reflections on the origin, evolution, and enduring impact of a journal created by and for students. From the outset, THĒMIS sought to give voice to the student body, promote rigorous legal education, and foster dialogue across generations. The interview revisits key milestones, challenges, and the current relevance of the journal. It also highlights opportunities to expand its international reach and preserve its core identity in a digital age. With a critical perspective, the founder emphasizes serious study, professional integrity, and civic commitment as essential foundations of legal vocation.